0301 Use of acetochlor and cancer incidence in the Agricultural Health Study Cohort. (23rd June 2014) - Lerro, Catherine; Koutros, Stella; Andreotti, Gabriella; Hines, Cynthia; Lubin, Jay; Zhang, Yawei; Beane Freeman, Laura
Abstract : Objectives: Since its registration in 1994, acetochlor, an herbicide licensed for use on corn, has been one of the most commonly used pesticides in the US. We evaluated use of acetochlor and cancer incidence in the Agricultural Health Study, a prospective cohort of licensed pesticide applicators. Method: During a telephone interview administered from 1999–2005, participants provided information on acetochlor use and other factors. Total lifetime days of acetochlor use were calculated and an intensity-weighting algorithm was applied that accounted for factors that modify exposure. We used Poisson regression to estimate relative risks (RR) and 95% confidence intervals (CI) for cancers that occurred from the time of interview through 2011 in Iowa and 2010 in North Carolina. We examined all cancer sites together, and individual sites with >10 exposed cases. Results: Among 33 484 men, 3234 incident cancers and 304 acetochlor-exposed cases occurred. An increased risk of lung cancer was observed among ever users of acetochlor (n = 23) (RR=1.57; CI=0.95–2.59) compared to never users, but there was no evidence of an exposure response trend (p-trend=0.30). Also, there was increased risk of colorectal cancer (n = 25) with high acetochlor use (RR=1.60; CI=0.97–2.65, p-trend=0.14). Conclusions: The associations between acetochlor use and colorectal and lung cancer are novel. However, due to lack of exposure-response trend, small number of exposed cases, and relatively short time between acetochlor use and cancer development, these findings warrant caution in interpretation and further investigation.